Clinical Performance of Three Commercial SARS‐CoV‐2 Rapid Antigen Tests for Community-Dwelling Individuals in a Tropical Setting - Morales-Jadán, Diana; Viteri-Dávila, Carolina; Castro-Rodriguez, Bernardo; Vallejo-Janeta, Alexander Paolo; Rivera-Olivero, Ismar A.; Perez, Franklin; Garcia-Bereguiain, Miguel Angel (Frontiers in Cellular and Infection Microbiology, 2022)
As COVID-19 pandemic still persist, the use of Rapid Diagnosis Antigen Test (RDAgTs) for SARS-CoV-2 detection have increased as some of the brands available in the market were certified for emergency use. RDAgTs are a fast and cheap tool for SARS-CoV-2 surveillance with potential to improve testing capacities in middle and low income countries compared to RT-qPCR. However, as the clinical performance of RDAgTs varies between the commercial brands available, evaluation studies are necessary. Moreover, the available evaluation have been done at high income countries while current SARS-CoV-2 transmission is mainly happening at developing countries. Many of those countries are located on tropical latitudes where cross reactivity with other infectious agents at high prevalence in those settings could happened compromising RDAgTs specificity. Moreover, unreported mutations and/or new SARS-CoV-2 variants may compromised RDAgTs sensitivity as genomic surveillance is limited in these settings. Here we describe a multicenter and manufacturer‐independent evaluation of the clinical performance and analytical sensitivity of three different RDAgTs brands available in South America from Rapigen (South Korea), SD-Biosensor (South Korea) and Certest (Spain) companies, compared to the gold standard RT-qPCR. A total number of 1,654 nasopharyngeals swabs from community dwelling individuals where included in the study, and 379 of them were SARS-CoV-2 positive by RT-qPCR. The overall sensitivity for each RDAgT was 79%, 64.2% and 45.8% for SD-Biosensor, Certest and Rapigen, respectively. The overall specificity for each RDAgT was 100%, 97.7% and 100% for SD-Biosensor, Certest and Rapigen, respectively. However, the limit of detection to achieve a sensitivity over 90% was substantially lower for Cerstest RDAgT (102 copies/mL) compared to SD-Biosensor (103 copies/mL) or Rapigen (106 copies/mL) RDAgTs. Additionally, Certest RDAgT also showed an improved sensitivity uo to 79.7% for symptomatic individuals. Finally, the slight reduction in specificity for Certest RDAgTs was only associated to one of the laboratories performing this study, pointing out the need of locally assessed evaluation for RDAgTs like this one carried out in Ecuador. In conclusion, the RDAgTs tested in this study are a fast, cheap and point of care tool for SARS-CoV-2 surveillance, realiable enough to detect SARS-CoV-2 infectious individuals.